THE EFFECT OF GIVING Spirulina plantesis FLOUR AND BUTTERFLY PEA FLOWER (Clitoria ternatea) FLOUR ON THE FOOD CONVERTION RATIO AND SURVIVAL RATE OF Channa pulchra FISH - Sadewo, Bayu Bagus; Firmani, Ummul; Safitri, Nur Maulida (Program Studi Akuakultur, Universitas Bangka Belitung, 2024)
The rise of the world of ornamental fish in Indonesia has become a business opportunity for various groups. One of them is the ornamental snakehead fish or Channa pulchra. This fish comes from Myanmar and was imported to Indonesia to meet the needs of the ornamental fish market. One of the factors that influence the success of a fish farming business is the FCR and SR values. The lower the FCR value and the higher the SR value, the better the sustainability of the cultivation business. To maintain FCR and SR values, a good quality feed supply is needed. The aim of this research is to determine the effectiveness of supplementing pelleted feed in the form of Spirulina flour and butterfly pea flower flour (Clitoria ternatea), which contain nutrients to support growth and immunity so that they can improve FCR and SR values. The methods used in this research are quantitative and experimental methods. The experimental design used was a completely randomized design (CRD) with 12 containers filled with 1 fish/container. Data were analyzed using the ANOVA test which was carried out with Duncan's advanced test. Observation parameters include FCR value, SR value and water quality. The results obtained showed that there was an effect of providing different additional feeds on the FCR value with the best treatment being treatment A with a value of 3.6 ± 0.61. Treatment B has a value of 5.35 ± 0.21 and treatment K has a value of 4.05 ± 0.53. Meanwhile, the SR value does not show any influence from providing additional feed which is different from the value of 100% for each treatment parameter. Water quality results include a salinity value of 0 ppt, DO 7.16 ± 0.68 mg/l and temperature 29.62 ± 0.82 °C. The water quality value is still considered safe for cultivation unless the temperature is too high which is thought to influence fluctuations in the FCR value.